PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN KEADILAN ORGANISASIONAL DI PT. SINAR BALI INDAH - Suarya Natha, Pande Putra; Dewi Adnyani, I Gusti Ayu (E-Jurnal Manajemen; Vol 6 No 7 (2017), 2017)
This research was conducted at PT. Sinar Bali Indah Denpasar. The purpose of this study was to determine the effect of transformational leadership style and organizational justice on job satisfaction in PT. Sinar Bali Indah Denpasar. The number of respondents in this study were 60 respondents to the census method. The data collection is done by interviews and questionnaires. The analysis technique used is multiple linear regression analysis. The results of this study indicate that transformational leadership style positive and significant impact on job satisfaction in PT. Sinar Bali Indah as well as organizational justice positive and significant impact on job satisfaction in PT. Sinar Bali Indah. PT leaders. Sinar Bali Indah must keep and always pay attention to how much motivation and concern felt by employees at PT. Sinar Bali Indah. Providing motivation and attention are equally important to provide that employee morale and can lead to increased job satisfaction on the employee at PT. Sinar Bali Indah Denpasar.
Keywords: transformational leadership, organizational justice, job satisfaction